(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the problem of interaction between language and religion. It reviews key scholarly works on the subject and presents various theoretical perspectives on the relationship between these two fundamental phenomena. The study attempts to analyze the nature of this interaction and argues for the recognition of “language and religion” as a distinct field of linguistic inquiry. The findings suggest that language and religion, while occupying opposite poles in the system of social consciousness, are deeply interconnected through their shared roots in human spirituality and culture.